2021
DOI: 10.3389/fpls.2021.640379
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhiza Improves Photosynthesis and Restores Alteration in Sugar Metabolism in Triticum aestivum L. Grown in Arsenic Contaminated Soil

Abstract: Contamination of agricultural soil by arsenic (As) is a serious menace to environmental safety and global food security. Symbiotic plant–microbe interaction, such as arbuscular mycorrhiza (AM), is a promising approach to minimize hazards of As contamination in agricultural soil. Even though the potential of AM fungi (AMF) in redeeming As tolerance and improving growth is well recognized, the detailed metabolic and physiological mechanisms behind such beneficial effects are far from being completely unraveled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 87 publications
2
24
0
Order By: Relevance
“…As regards microbe symbionts, AMF have a role as a biofertilizer and serve to support a plant’ quality advantage in agroecosystems [ 10 ]. At most, AMF symbiosis is able to improve a plant’s physiological traits (i.e., photosynthetic efficiency, plant biomass, and yield [ 11 , 12 , 13 ]), and AMF also influence N uptake into the host plant [ 14 , 15 ]. Nonetheless, the N content in the host plant depends on the AMF taxa as observed with Acaulospora scrobiculata, Glomus etunicatum, G. mosseae, and G. versiforme symbiosis in walnut [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As regards microbe symbionts, AMF have a role as a biofertilizer and serve to support a plant’ quality advantage in agroecosystems [ 10 ]. At most, AMF symbiosis is able to improve a plant’s physiological traits (i.e., photosynthetic efficiency, plant biomass, and yield [ 11 , 12 , 13 ]), and AMF also influence N uptake into the host plant [ 14 , 15 ]. Nonetheless, the N content in the host plant depends on the AMF taxa as observed with Acaulospora scrobiculata, Glomus etunicatum, G. mosseae, and G. versiforme symbiosis in walnut [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic is one of the most toxic elements in nature, seriously endangering plants, animals, and even humans [102]; As is generally found in all crustal rocks but can be released due to natural factors or human activities in the environment [102,103]. Among the natural factors that cause the release of As in nature are volcanic activity and weathering of rocks [104], but the human factors that cause the release of As in the environment are mining, fossil fuels, tannery, pesticides, herbicides, and chemical fertilizers [102][103][104]. The most important cause of arsenic poisoning is contaminated groundwater found in Bangladesh, Italy, Argentina, Hungary, India, China, Mexico, Chile, and the United States [105,106].…”
Section: Arsenic (As)mentioning
confidence: 99%
“…Gupta et al reported that As affects growth and productivity due to the morphological, biochemical, and physiological changes it causes in plants [104]. As in plants reduces transpiration rate and leaf water potential, chlorophyll content (Chl), nutrient uptake, CO 2 stabilization rate, photosystem II activity, photosynthesis rate, heat loss capacity, carbon splitting, and sugar metabolism [107][108][109][110][111][112]; also, one of the most dangerous biochemical effects of As is the production of intracellular reactive oxygen species (ROS), which causes irreversible damage to DNA, lipids, carbohydrates, and proteins [107].…”
Section: Arsenic (As)mentioning
confidence: 99%
“…HM-contaminated soils can be redeemed and revegetated by using AMF that can potentially expedite the phytostabilization and phytoextraction process (Khalid et al, 2021). The potential of AMF as an ameliorator of HM toxicity has been well-proved and promoted (Christie et al, 2004;Bai et al, 2008;Merlos et al, 2016;Sharma et al, 2017;Gupta et al, 2021). Fungus-assisted phytoremediation is deemed as the most befitting and ecofriendly technology for the redemption of HM polluted soil (Khalid et al, 2021).…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…Abiotic stresses, such as salinity, drought, and heavy metals (HMs), result in a 70% reduction in global crop yield worsening the dwindling equilibrium between crop production and exponential population growth (Singh et al, 2016). In addition to this, abiotic stresses, particularly salinity and HMs, depress the nutrient availability in soil and lead to nutritional disorders in plants (Juniper and Abbott, 1993;Evelin et al, 2012;Gusman et al, 2013;Gupta et al, 2021). Soil salinity and HM contamination have been demonstrated to limit the accumulation of minerals, such as Ca, Fe, Mg, and Zn in edible parts of crop plants (Gusman et al, 2013;Chakraborty et al, 2016;Alam et al, 2019;Liu et al, 2020), consequently reducing the nutritive value of the crops.…”
Section: Introductionmentioning
confidence: 99%